(untitled) (Zaporizhzhia Historical Review, 2021)
The article is devoted to historiography of a socio-economic and political problematics of the Postclassic Maya society, its features, periodization, main characteristic features of its every stage and connection with others social disciplines and natural sciences. Such generalization enables to expand scientific interest to a new directions of research of the Maya civilization.